Stroke rehabilitation and research: consideration of the role of the cortico-reticulospinal system. (3rd April 2018) - Silva, Augusta; Vaughan-Graham, Julie; Silva, Claudia; Sousa, Andreia; Cunha, Christine; Ferreira, Rosália; Barbosa, Pedro Maciel
Abstract: A cerebrovascular accident, otherwise known as stroke, has the potential to damage multiple areas within the brain affecting descending motor control via a multitude of pathways resulting in a wide variety of movement problems. The cortico-reticulospinal system, one of the largest motor systems, is frequently affected, compromising its output, resulting in postural control deficits. The identification of clinically relevant instruments and scales to document and evaluate recovery in post-stroke patients is vital. However, the availability of such measures and scales which take into consideration the role of postural control as an integral component of functional movement performance are scarce. This paper will critically discuss the importance of integrating current neuroscience and motor control knowledge in order to better understand and describe the clinical presentation of persons post-stroke such that the effectiveness of stroke rehabilitation can be appropriately measured.